IMPLEMENTATION OF THE DIRECT METHOD IN OVERCOMING THE LEARNING DIFFICULTIES OF ADHD IN STUDENTS AT PUTERA ASIH SLB KEDIRI CITY - Muhammad Syahrul Munir; Muhammad Akhsanul Muhtadin; Ali Muchasan (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
ADHD (Attention Deficit/Hyperactivity Disorder) is characterized by persistent attention deficit and hyperactivity-intensive disorder. ADHD behaviors are often seen as not being able to pay attention. Easily distracted, cannot sit still, often leaves the seat, often runs, and his body keeps wanting to move. This research aims to find out suitable learning methods in overcoming ADHD (Attention Dificit/Hyperactivity Disorder) students. This research was conducted at SLB Putera Asih Kota Kediri. This research, the type of research used is qualitative. The data collection method used to determine the learning method is field observation. Field observations are conducted with interviews in order to obtain oral or written information from all information obtained from respondents. Analysis is carried out before the researcher collects data and continues throughout the research until all data is collected. Based on the data analysis conducted, it can be concluded that the direct method learning method can overcome the learning difficulties of ADHD (Attention Dificit/Hyperactivity Disorder) children.